EVALUASI PENERAPAN MANAJEMEN CARA PEMBENIHAN IKAN YANG BAIK (CPIB) PADA UNIT PEMBENIHAN UDANG DINAS KELAUTAN DAN PERIKANAN PROVINSI SULAWESI SELATAN DI BOJO KABUPATEN BARRU - Hartati Hartati; Jayadi Jayadi; Andi Tamsil (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2019)
Evaluation of the implementation of good management of fish hatchery (CPIB) at the shrimp hatchery unit of the Departmen of marine and fishery in south Sulawesi province in Bojo, Barru regensy. This research was conducted in February 2019 until April 2019 at the shrimp hatchery until of the Departmen of Marine and Fisheries in south Sulawesi in Bojo, Barru regency. The hatchery unit is a barometer of other shrimp hatcheries in Barru regency in particular and those in South Sulawesi province in general. Based on the results of research using the analysis method (t test) and linear regression shows that the implementation of good management of fish hatchery (CPIB) has an excellent effect on shrimp seed production and internal management factors that affect almost 70% of successful seed production are water quality management, master management, feed management, larvae management and personnel management and the remaining around 30% of production is influenced by external factors such as environment and others. To increase the production of shrimp seed in hatchery units, is it necessary to seek for adjustments and performance enhancements and still be giuded by the method of good hatchery (CPIB) in implementing the 5 production management steps as internal factors greatly determine the success level of seed production both in quantity and quality. Keyword : Shrimp hatchery, regulation, implementation, managemen CPIB